The procurement and use of knappable glassy volcanic raw material from the late Pleistocene Pilauco site, Chilean Northwestern Patagonia. Issue 5 (28th March 2019) - Navarro‐Harris, Ximena; Pino, Mario; Guzmán‐Marín, Pedro; Lira, María Paz; Labarca, Rafael; Corgne, Alexandre
Abstract: In this study we used a multidisciplinary approach, coupling morphological, geological, geochemical, and statistical analyses to investigate the provenance of rhyodacitic and dacitic glass knapped at the Pilauco site (40°34′11" S, 73°06′17" W; 13, 570 ± 70–12, 540 ± 90 14 C year BP) in northwestern Chilean Patagonia. A morphotechnological analysis was performed on the entire lithic assemblage, which is composed of cores, retouched and unretouched unifacial flakes, and small pieces of debitage, some of them closely associated with Notiomastodon aff. N. platensis gomphothere bones. Sixty‐two archeological and geological samples were analyzed by inductively coupled plasma mass spectrometry revealing a wide range of basaltic to rhyodacitic compositions. The archeological knappable dacitic and rhyodacitic glasses were recovered from pebbles deposited mainly on a beach away from the site, as deduced by the presence of minute and dense crescentic percussion marks on the cortexes. Geochemical trace element analysis suggests that the Puyehue–Cordón Caulle Volcanic Complex is the most likely source for the volcanic glass artifacts at Pilauco. The new morphotechnological and provenance record and improved stratigraphic sequences highlight the Pilauco site as an important contribution for the diversity of the South American geoarchaeological context.